Experiment On EDM Machining For Advance Engineering Material Using Taguchi Method - Mustafa, Mohammed Irfan (Universiti Sains Malaysia, 2005)
Electro-discharge machining (EDM) technique is widely used for machining hard metals and for performing specific tasks which cannot be achieved using conventional technique. The most frequently used industrial application of die-sinking is mould fabrication. In this project, the main purpose is to optimize the quality of cut for tool steel (hardened) using Taguchi single response and multiple response performance characteristic. The orthogonal array, single and multi-response signal-to-noise ratio and analysis of variance are employed to study the cutting characteristic in EDM. The study needs to optimize three parameters; current, gap and pulse duration to get best surface roughness, material removal rate and electrode wear rate. The optimal combination of parameters obtained in both single response and multiple response performance characteristic shows significant improvement in cutting quality. Taguchi method is an effective approach to optimized process parameter with given cutting characteristic.